EVALUATING THE SUITABILITY OF ALUMIDE TOOLING FOR INJECTION MOULDING OF DIFFERENT POLYMERS - Combrinck, Jacques; van der Walt, Kobus; Booysen, Gerrie; de Beer, Deon (The South African Journal of Industrial Engineering, 2018)
This paper describes the possibility of using laser-sintered Alumide® as an alternative material for producing rapid tooling (RT) inserts. To determine the durability of Alumide® inserts for the injection moulding (IM) process, a product with geometrical features was developed, and Alumide® inserts were manufactured. Polypropylene (PP), acrylonitrile-butadiene-styrene (ABS), polycarbonate (PC), and polyamide 6 (PA 6) were used for IM trials with the Alumide® inserts. From these trials, it was concluded that polymer materials with a processing temperature of about 230 ºC, similar to PP and ABS, can be used with Alumide® inserts as RT inserts for the IM process.